(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay analyzes the recent decision n. 33 of 2021 of the Constitutional Court in the field of surrogate motherhood and best interests of the child, having particular regard to the different role played by the merit Courts (which remains subject to the law in adjudicating concrete cases) and Parliament (which has the constitutional power – and the duty as well – to regulate those very delicate issues from a more general perspective).